Chinese and Indian migrant mothers’ perceptions and experiences of utilising maternal and early childhood healthcare services in Aotearoa New Zealand: a qualitative descriptive study - Anjali Bhatia; Hongxia Qi; Nadia A. Charania (Kōtuitui)
Although the health system in Aotearoa New Zealand is based on universalism and equity, disparities exist in the uptake and quality of health care for ethnic-migrant mothers and their children. This qualitative descriptive study explored the perceptions and experiences of Chinese and Indian migrant mothers (N = 24) accessing maternal and early childhood healthcare services. Semi-structured interviews and focus groups were conducted and data were analysed using reflexive thematic analysis. Three themes were generated. Migrant mothers displayed limited awareness of services available for themselves and their children, and experienced difficulties navigating the complex and fragmented health system. Transnational ties influenced mothers’ expectations of care and health seeking practices for themselves and their children. Mothers shared suggestions for a system that is inclusive of migrants’ needs, such as offering orientation sessions to raise awareness and ease navigation challenges, having interpreters available and translated resources to support language challenges, and improve postpartum support as mothers adapt to motherhood. To improve health equity, it is important that national policy supports improvements to the health system to address the challenges faced by ethnic-migrant families when navigating health services.